Analisis Bibliometrik Penggunaan Model Game Based Learning (GBL) Pada Pembelajaran PAI Tahun 2022-2024 Menggunakan VOSViewer - Nor Aida; Santiani (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This article was prepared to determine: (1) a map of the development of the number of publications examining learning using game based learning models in PAI learning; (2) knowing which scientific articles have the highest number of citations; (3) knowing the development map of scientific publications based on keywords. The method used in this research is bibliometric analysis using the VOSViever application. The data source used in this research is the Publish or Perish application to obtain scientific articles in the Google Scholar database with the keywords game based learning model in PAI learning, with categories of article title, abstract, keywords in the 2022-2024 range. Search results show that there are 170 scientific articles that match keywords based on the Harzing's Publish or Perish application. The results of the research show that research on learning using the game-based leaning model in PAI learning in 2022-2024 is the highest in Google Scholar, occurring in 2023 with the number of publications 73. Research on learning using the game-based learning model in PAI learning continues to develop from year 2022 to 2023 and will decrease in 2024. In 2022 there were 52 articles, 73 articles in 2023, and 45 articles in 2024. This topic is often discussed and researched under the keyword Game Based learning but regarding the game based learning model in learning PAI is still few and rarely researched.